Evaluation of Mode and Psychiatric Co-morbidity of Intentional Self Harm: A Hospital Based Study - Shrestha, Rajesh; Lamichhane, Ram; Sharma, Bhaskker (Journal of Lumbini Medical College, 2020)
Introduction: Intentional self harm is a potentially self injurious action with a non-fatal outcome for which there is evidence, either explicit or implicit, that the individual intended to kill himself or herself. Suicide is a fatal act of self-injury (self harm) undertaken with more or less conscious self destructive intent. There has been an increase in the number of patients presenting with attempted suicide in the emergency settings of hospitals. This study aimed to explore socio-demographic characteristics, pattern of attempts, psychiatric diagnosis, psychosocial and personality factors among survivors of suicide attempt presenting to a tertiary care hospital. Methods: The study included 100 survivors of intentional self harm registered over a period of six months visiting a tertiary care hospital. The cases directly presented to Psychiatry department and were referred from medical and other departments for psychiatric evaluation. They underwent evaluation by consultant psychiatrist and received appropriate interventions. Results: Majority of the victims were female (73%), belonging to the age group of 20-40 years. The most common method of attempt was self poisoning with pesticides (65%) followed by hanging (16%) and overdose of drugs (7%). Most of the attempts (68%) were impulsive in nature. Mental illness was diagnosed in (65%) of the cases, mainly depressive disorder (51%), and personality disorder (10 %). Most of the attempts (67%) were triggered by psycho-social factors. Conclusion: The pattern shows predominance of female gender, young age group, a role of mental illness, impulsivity and psychosocial factors in intentional self harm.